Postgraduate education network: theory and practice in europe and Russia - J. D. Artamonova; A. L. Demchuk; V. V. Moiseeva (Moscow Polytechnic University, 2022)
This article presents the current state of the world practice of higher education institutions networking at PhD level, analyzes the experience of the European and Russian higher education institutions in organizing such a networking, points out the key issues and suggests solution options.